Physical Properties as Modal Operators in the Topos Approach to Quantum Mechanics - Freytes Solari, Hector Carlos (2014)
In the framework of the topos approach to quantum mechanics we give a representation of physical properties in terms of modal operators on Heyting algebras. It allows us to introduce a classical type study of the mentioned properties.